2007
DOI: 10.1007/s10620-006-9367-y
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Rebamipide on NSAID-Induced Gastric Mucosal Injury and Reduction of Gastric Mucosal Blood Flow in Healthy Volunteers

Abstract: The precise mechanisms of acute damage and the role of gastric mucosal blood flow in gastric mucosal injury induced by nonsteroidal anti-inflammatory drugs (NSAIDs) remain uncertain. The aim of this study was to evaluate the preventive effect of rebamipide on gastric mucosal injury and reduction of gastric mucosal blood flow (GMBF) after ibuprofen administration. Twenty healthy volunteers were randomized two groups. The rebamipide group took ibuprofen, 1800 mg/day, and rebamipide, 100 mg t.i.d., for 7 days. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 27 publications
0
30
1
2
Order By: Relevance
“…Rebamipide is a well-known antiulcer drug that has many biological activities in the gastric The basal healing rate of the combination group was significantly greater than that of the PPI group for large-sized ulcers, but there were no significant differences for normal-sized ulcers (b). Combination, PPI plus rebamipide; normal-size, ulcer area \1,200 mm 2 ; large-size, ulcer area C1,200 mm 2 ; NS not significant mucosa, such as stimulating angiogenesis by activating pro-angiogenic growth factors [14], increasing the biosynthesis of endogenous prostaglandins [15], and inhibiting neutrophils activated by H. pylori [16,17] and non-steroidal anti-inflammatory drugs [18,19]. Iijima et al [20] also reported that rebamipide administration increased gastric mucus secretion in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Rebamipide is a well-known antiulcer drug that has many biological activities in the gastric The basal healing rate of the combination group was significantly greater than that of the PPI group for large-sized ulcers, but there were no significant differences for normal-sized ulcers (b). Combination, PPI plus rebamipide; normal-size, ulcer area \1,200 mm 2 ; large-size, ulcer area C1,200 mm 2 ; NS not significant mucosa, such as stimulating angiogenesis by activating pro-angiogenic growth factors [14], increasing the biosynthesis of endogenous prostaglandins [15], and inhibiting neutrophils activated by H. pylori [16,17] and non-steroidal anti-inflammatory drugs [18,19]. Iijima et al [20] also reported that rebamipide administration increased gastric mucus secretion in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this study has been able to show that rebamipide might be effective at preventing NSAIDinduced small intestinal injuries to a certain extent. Rebamipide has been used across Asia for the treatment of gastric ulcers and gastric lesions such as erosions and edema caused by acute gastritis [14,17,22]. It has been well documented that rebamipide increases endogenous prostaglandin levels, scavenges free radicals, and suppresses inflammation in the gastric mucosa [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…[8] In the study by Kіm et al, [9] twenty healthy volunteers were randomized two groups. The placebo group took ibuprofen, 600 mg t.i.d., and placebo for 7 days.…”
Section: Resultsmentioning
confidence: 99%